2018
DOI: 10.1007/s12561-018-9214-7
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Sets of Potential Transplants in a Kidney Paired Donation Network

Abstract: In kidney paired donation (KPD), incompatible donor-candidate pairs and non-directed (also known as altruistic) donors are pooled together with the aim of maximizing the total utility of transplants realized via donor exchanges. We consider a setting in which disjoint sets of potential transplants are selected at regular intervals, with fallback options available within each proposed set in the case of individual donor, candidate or match failure. We develop methods for calculating the expected utility for suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Step (3b). In [16], we have investigated efficient methods to evaluate the expected utilities required in Step (2b). The IP problem that corresponds to Step (3b) becomes more complex as the number of potential sets to select increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Step (3b). In [16], we have investigated efficient methods to evaluate the expected utilities required in Step (2b). The IP problem that corresponds to Step (3b) becomes more complex as the number of potential sets to select increases.…”
Section: Discussionmentioning
confidence: 99%
“…Some additional work on the third type can be found in [16,13,14]. When failure probability is moderate, it has been demonstrated that such locally relevant subgraphs can lead to greatly improved selection processes that yield many more realized transplants, by as much as, 8% compared to fallbacks within cycles and chains [13].…”
Section: Overview Of Prior Researchmentioning
confidence: 99%
“…In recent work we have shown considerable advantage of the approach based on LRSs as compared to the simple selection of cycles and chains. Over time, schemes that utilize LRSs, accounting for the uncertainty and the possibility to pursue fallback options within a failed exchange, yield higher numbers of realized transplants in KPD microsimulation models than schemes that only consider simple cycles and chains, with gains of roughly 40% when compared to the simplest settings [27,28].…”
Section: Optimizationmentioning
confidence: 99%
“…Optimization can be further extended beyond selection of simple cycles or chains to encompass fallback options in case of non-viability [24][25][26]. We have previously investigated the incorporation of these considerations into KPD optimization through simulation, where formidable gains in realized utility were observed [27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation